Drying methods, carrier materials, and length of storage affect the quality of xylooligosaccharides. (September 2019) - Zhang, Liangqing; Qiu, Jiarong; Cao, Xuejuan; Zeng, Xianhai; Tang, Xing; Sun, Yong; Lin, Lu
Abstract: Four drying methods such as freeze drying, vacuum drying, hot-air drying, and spray drying, with or without carriers (maltodextrin and gum arabic) were applied to evaluate their influence on the physicochemical properties, microstructures, and storage stability of the resulting xylooligosaccharides (XOS) products. The glass transition temperature ( T g ), freezable water content, water activity, water sorption isotherms, microstructure (characterized by XRD, FT-IR, and SEM), chemical quality, and shelf life were mainly studied. The results showed that freezable water content was negatively correlated with T g . T g and monolayer water content ( X m ) greatly affect the processability and stability of the XOS product, which had a further impact on the microstructure of the product during the storage. For comprehensive consideration, the freeze-dried product with 32–50% maltodextrin and 6–18% gum arabic has higher T g and lower X m, and storage stability are relatively good, which can be used as the best conditions for drying the crude XOS liquid. Graphical abstract: Image 1 Highlights: Four drying methods were applied to dry crude xylooligosaccharides liquid. The relationship between water state and glass transition temperature was revealed. Moisture adsorption isotherms and monolayer water content were discussed in depth. Drying methods and carrier materials significantly affected the product quality. Water activity and glass transition temperature greatly impacted on shelf life.